HIV continuum of care in Europe and Central Asia. Issue 7 (24th January 2017) - Drew, RS; Rice, B; Rüütel, K; Delpech, V; Attawell, KA; Hales, DK; Velasco, C; Amato‐Gauci, AJ; Pharris, A; Tavoschi, L; Noori, T
Abstract : Objectives: The European Centre for Disease Prevention and Control (ECDC) supports countries to monitor progress in their response to the HIV epidemic. In line with these monitoring responsibilities, we assess how, and to what extent, the continuum of care is being measured across countries. Methods: The ECDC sent out questionnaires to 55 countries in Europe and Central Asia in 2014. Nominated country representatives were questioned on how they defined and measured six elements of the continuum. We present our results using three previously described frameworks [breakpoints; Joint United Nations Programme on HIV/AIDS (UNAIDS) 90‐90‐90 targets; diagnosis and treatment quadrant]. Results: Forty countries provided data for at least one element of the continuum. Countries reported most frequently on the number of people diagnosed with HIV infection (37; 93%), and on the number in receipt of antiretroviral therapy (ART) (35; 88%). There was little consensus across countries in their approach to defining linkage to, and retention in, care. The most common breakpoint (>19% reduction between two adjacent elements) related to the estimated number of people living with HIV who were diagnosed (18 of 23; 78%). Conclusions: We present continuum data from multiple countries that provide both a snapshot of care provision and a baseline against which changes over time in care provision across Europe and Central Asia may be measured. To better inform HIV testing and treatment programmes, standard data collection approaches and definitions across the HIV continuum of care are needed. If countries wish to ensure an unbroken HIV continuum of care, people living with HIV need to be diagnosed promptly, and ART needs to be offered to all those diagnosed.